1999
DOI: 10.1103/physrevb.60.15617
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the outermost layer betweenTaB2(0001)andHfB

Abstract: Atomic and electronic structures of TaB 2 (0001) and HfB 2 (0001) surfaces are investigated with use of the first-principles pseudopotential calculations. Our calculated surface formation energies indicate that the graphitic-boron-terminated TaB 2 (0001) surface is energetically more favorable, whereas the HfB 2 (0001) surface prefers termination with a close-packed Hf layer. These findings are consistent with experimental facts. We have also found the difference in the surface relaxation between them. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 21 publications
12
26
1
Order By: Relevance
“…The binding energies of the B-σ bonds of ZrB 2 (0001) is about 1 eV lower than those of NbB 2 (0001) and TaB 2 (0001), which are related with the difference of the E F level. The surface electronic structures of MB 2 (0001) observed in this work were consistent with the surface structures determined experimentally, and the theoretical results by Yamamoto et al [4].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The binding energies of the B-σ bonds of ZrB 2 (0001) is about 1 eV lower than those of NbB 2 (0001) and TaB 2 (0001), which are related with the difference of the E F level. The surface electronic structures of MB 2 (0001) observed in this work were consistent with the surface structures determined experimentally, and the theoretical results by Yamamoto et al [4].…”
Section: Discussionsupporting
confidence: 91%
“…The surface properties have been widely investigated experimentally and theoretically [4][5][6][7]. The surfaces of ZrB 2 (0001) and HfB 2 (0001) are terminated with the metal layer [8,9], and the surfaces of NbB 2 (0001) and TaB 2 (0001) are terminated with the B layer [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experiments and theoretical calculations have demonstrated that the terminated (0 0 0 1) surfaces of HfB 2 and TaB 2 are different [14][15][16]. For HfB 2 , the Hf-terminated (0 0 0 1) surface is more favorable than B-terminated surface, while B-terminated surface is favorable for TaB 2 .…”
Section: Methodsmentioning
confidence: 96%
“…Among the surfaces of HfB 2 and TaB 2 crystals, the (0 0 0 1) surfaces have been the most studied to date. However, the Hf-terminated (0 0 0 1) surface of HfB 2 is different from the B-terminated (0 0 0 1) surface of TaB 2 [14]. The (0 0 0 1) surfaces exhibit different chemical reactivity.…”
Section: Introductionmentioning
confidence: 96%